Improvement of H2-rich gas production with tar abatement from pine wood conversion over bi-functional Ca2Fe2O5 catalyst: Investigation of inner-looping redox reaction and promoting mechanisms. (15th February 2018) - Sun, Zhao; Chen, Shiyi; Russell, Christopher K.; Hu, Jun; Rony, Asif H.; Tan, Gang; Chen, Aimin; Duan, Lunbo; Boman, John; Tang, Jinke; Chien, TeYu; Fan, Maohong; et al.
Graphical abstract: Highlights: A modified sol-gel method was used for the preparation of calcium ferrites. Ca2 Fe2 O5 was found to facilitate tar abatement and biochar conversion. Ca plays an essential role in achieving steam oxidation from Fe 0 to Fe 3+ . An inner-looping redox reaction and promoting mechanisms are proposed. Abstract: The objective of this research was to find cost-effective inner-looping redox-reaction-based biomass conversion catalysts by screening five Fe-containing materials through the integration of pine wood pyrolysis and gasification. All the evaluation tests are conducted in a fixed bed reactor under atmospheric pressure. The effect of temperature, water injection rate (steam/biomass ratio), catalyst loading, and reaction time on pine wood conversion performances was investigated. Ca2 Fe2 O5 catalyst was found to facilitate H2 -rich gas production, tar abatement, and carbon conversion. The maximum H2 yield of 7.12 mol·H2 /kg·Biomass was obtained in the first 10 min of gasification, which increased H2 yield by 78.98% compared to biomass gasification under the water injection rate of 0.10 mL/min and catalyst load amount of 10 wt.% at 850 °C. Moreover, the hydrogen utilization, carbon conversion, and total gas yield of the process due to the use of Ca2 Fe2 O5 increase by 13.4%, 17.3%, and 11.7%, respectively. Continuous high yields of H2 -enriched syngas were observed during the cyclic stability tests, indicating significant activity and redox durability of Ca2 Fe2 O5 . The catalyst characterization using BET, XRD, H2 -TPR, SEM/EDS, and TEM revealed that Ca2 Fe2 O5 is stable when tested cyclically, which results from the existence of Ca 2+ in Ca2 Fe2 O5 . The bi-functional Ca2 Fe2 O5 catalyst provides a novel way of inner-looping redox reaction for the continuous conversion of biomass.